2019
DOI: 10.1007/s00415-019-09597-2
|View full text |Cite
|
Sign up to set email alerts
|

Early presentation of urinary retention in multiple system atrophy: can the disease begin in the sacral spinal cord?

Abstract: Lower urinary tract (LUT) dysfunction presents early in multiple system atrophy (MSA), usually initially as urinary urgency, frequency and incontinence, and voiding difficulties/urinary retention becomes apparent over time. We have observed a subset of patients who instead presented initially with urinary retention requiring catheterisation. At presentation, these patients had only subtle neurological signs that would not fulfil the diagnostic criteria of MSA; however, the anal sphincter electromyography (EMG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…The vacuolar neurons and neurites revealed in the thoracic, lumber and sacral spinal cord. This was similar other neuropathology of neurodegenerative diseases [34][35][36][37][38][39]. It could be speculated that the aging-related N-d alteration was neuropathological degeneration.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The vacuolar neurons and neurites revealed in the thoracic, lumber and sacral spinal cord. This was similar other neuropathology of neurodegenerative diseases [34][35][36][37][38][39]. It could be speculated that the aging-related N-d alteration was neuropathological degeneration.…”
Section: Discussionsupporting
confidence: 80%
“…Autonomic dysfunctions of orthostatic hypotension, urinary incontinence and constipation are common symptoms in neurodegenerative demented patients [38]. Neurodegeneration of the sacral spinal cord may be relevant the onset of multiple system atrophy [39]. Onset of urinary retention in multiple system atrophy can begin in the sacral spinal cord [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although he lacked a motor disorder, all these features suggested possible MSA-C [1][2][3]. We started him on clean, intermittent self-catheterization.…”
Section: Case Reportmentioning
confidence: 99%
“…Multiple system atrophy (MSA) is a progressive degenerative neurological disorder clinically defined as a combination of motor (parkinsonian MSA and/or cerebellar MSA [MSA-C]) and autonomic (orthostatic and/ or bladder) disorders by the second consensus statement on the diagnosis of MSA [1]. In contrast, recent prospective cohort studies have shown that up to 18.2% of MSA patients start with bladder dysfunction alone that might last up to 7 years [2,3], suggesting that the disease process of alpha-synuclein aggregation might begin in the sacral spinal cord [4]. However, the question arises as to whether we are able to diagnose very early, "premotor" MSA.…”
Section: Introductionmentioning
confidence: 99%